Extension in geothermal fields between the Imperial and Mexicali Valleys revealed by 2D seismic imaging and joint gravity-aeromagnetic modeling. (January 2021) - Reyes-Martínez, Carlos Simón; González-Escobar, Mario; Montalvo-Arrieta, Juan Carlos; Tapia, Fernando Velasco; Jenchen, Uwe
Highlights: The seismic reflection method has been little used in volcanic environments and the exploration of geothermal resources. 2D gravimetric and aeromagnetic models constrained by seismic data showing zones of sediments metamorphosed. three domains for future geothermal exploration in the Mexicali Valley. Abstract: We present 2D seismic reflection images covering 64 km along with 62.5 km of gravity and aeromagnetic models. The modeled region extends from the Cerro Prieto volcano, across the Mexicali Valley, Baja California, Mexico, to the USA-Mexico border near Pilot Knob, California, USA. The seismic images illustrate the shallow structure to the north of the Cerro Prieto basin, and a seismic reflector in the northeastern part of the profiles corresponds to the metamorphic basement. Some major faults were identified through discontinuities in the reflectors (Dunes and San Luis faults), while others (Michoacán, Imperial, and Calipatria faults) are expressed as chaotic low-amplitude anomalies in the seismic images. 2D gravimetric and aeromagnetic models constrained by seismic data demonstrate the presence of zones of sediments metamorphosed by hydrothermal alteration fronts due to major faults and intrusions. We present for the first time a geologic model supported by geophysical data that cover transversely the entire Mexicali Valley. Finally, we identify three domains for future geothermal exploration in the Mexicali Valley, supported by the analytic signal of the aeromagnetic data after reduction to the pole and seismic reflection profiles from previous papers.